THE CONFLUENCE OF GENDER IDENTITIES AND CULTURAL HERITAGE: INVESTIGATING THE INFLUENCE ON HEALTH BEHAVIOURS AND SOCIAL DETERMINANT - R, Visnudharshana; S, Henry Kishore (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Traditional gender roles dictate that men engage in physically demanding activities while women are often relegated to domestic tasks, a dynamic that profoundly impacts health behaviours and outcomes in many cultures. This paper delves into the intricate confluence of gender identities and cultural heritage, scrutinizing their collective influence on health behaviours and social determinants. It posits that both gender norms and cultural expectations are pivotal in shaping individual lifestyle choices, risk behaviours, and overall health outcomes. Through a comprehensive review of existing literature, this study elucidates how intersecting identities create a complex web of influences that either exacerbate or mitigate health disparities. By analysing diverse cultural contexts, the paper highlights how specific cultural practices and gender roles interplay to affect physical activity, dietary habits, mental health, and substance use. The findings underscore the necessity for culturally sensitive public health strategies that acknowledge and address these multifaceted interactions. Moreover, the study advocates for a nuanced understanding of intersectionality to inform policy interventions aimed at reducing health inequities. This research contributes to the broader discourse on health equity, offering insights that are crucial for developing inclusive health.